2014
DOI: 10.1038/srep03855
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optical gyroscope using active Long-range surface plasmon-polariton waveguide resonator

Abstract: Optical gyroscopes with high sensitivity are important rotation sensors for inertial navigation systems. Here, we present the concept of integrated resonant optical gyroscope constructed by active long-range surface plasmon-polariton (LRSPP) waveguide resonator. In this gyroscope, LRSPP waveguide doped gain medium is pumped to compensate the propagation loss, which has lower pump noise than that of conventional optical waveguide. Peculiar properties of single-polarization of LRSPP waveguide have been found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…Fig. 5(b) shows the coupling efficiency of ARCs and its corresponding microspheres,which is the key factor for the limit sensitivity of ROG [26].The coupling efficiency of ACRs remains around 70% calculated using formula [27], which is the same as microsphere. Thus, compare to the corresponding microsphere, the ARC with deformation degree η¼8% holds the same scale Q-values and coupling efficiency, but a single spectrum peak (fundamental mode).…”
Section: Resultsmentioning
confidence: 95%
“…Fig. 5(b) shows the coupling efficiency of ARCs and its corresponding microspheres,which is the key factor for the limit sensitivity of ROG [26].The coupling efficiency of ACRs remains around 70% calculated using formula [27], which is the same as microsphere. Thus, compare to the corresponding microsphere, the ARC with deformation degree η¼8% holds the same scale Q-values and coupling efficiency, but a single spectrum peak (fundamental mode).…”
Section: Resultsmentioning
confidence: 95%
“…shot noise limited sensitivity (SNLS) and spontaneous emission limited sensitivity (SELS). In addition to Ref 13,. the spontaneous emission not only produces an uncertainty on the detection of the light frequency in the gyroscope which results in SELS, but also import a noise with a certain power into the gyroscope system.…”
mentioning
confidence: 94%
“…The SPPs, whose attractiveness comes from their useful surface propagation, confinement, and wavelength properties, are utilized in a wide variety of applications, such as subwavelength control of light [5,6], nanophotonic devices [7][8][9][10], lasers [11,12], novel materials [13][14][15], and nonlinear interactions [16]. Recent studies have further suggested the existence of entirely new SPP modes, including backward-propagating SPPs similar to fields encountered in negative-index materials at both single boundaries [17] and metallic films [18].…”
Section: Introductionmentioning
confidence: 99%